Revitalizing Islamic Holistic Education for Gender Role Balance in the Disruption Era - Primarni, Amie; Qadir, Wail Abdul; Arifin, Syamsul; Srihartini, Yusi; Makmudi, Makmudi (LP. Ma'arif Janggan Magetan, 2024)
The disruption era has significantly transformed gender roles in families, society, and professional sectors, presenting challenges in maintaining role balance while adhering to Islamic values. This study explores how Islamic holistic education can address these challenges by analyzing the concept’s role in fostering gender role harmony. Using a qualitative approach with descriptive-analytical methods, the research draws on library research, document analysis, and selective interviews with Islamic education practitioners. Content and thematic analysis were applied to examine classical texts and contemporary practices. Findings indicate that Islamic holistic education promotes a balanced and just gender role framework through the integration of spiritual, moral, intellectual, and social dimensions, fostering mutual respect and role complementarity between men and women. The study also highlights case examples, particularly from pesantren and community-based educational programs, which demonstrate practical implementation of gender-inclusive strategies. These programs empower both male and female learners to participate actively in leadership and decision-making, reflecting Sharia-compliant equality. Thus, the research contributes to theoretical developments in Islamic education and gender studies, while offering actionable strategies for educators and policymakers. Holistic Islamic education emerges as a viable and contextual solution to the evolving gender dynamics in the disruption era, bridging tradition with modern societal needs.